A Book Review “Becoming Community-Engaged Educators: Engaging Students Within and Beyond the Classroom Walls” - Siti Tamah (Beyond Words, 2022)
The book under review is a compilation of reflective writings from seven great educators. This book is really worth reading since each educator has included some reflection questions to complement the life narrative they joyfully share. It not only tells stories, but it also prompts my own contemplation. My own reflection has brought about a three-sentence plea: “When teachers teach and students learn, it is just a classroom. When teachers teach and both teachers and students learn, the classroom becomes alive. Yet, when teachers teach and communities are engaged, the classroom is truly revived”. Anita Lie focuses on poverty lessening while Joel Jablon tells how he becomes a ‘radically open’ person. Yoshi Grote highlights the quality of being an admiring teacher. The necessity for religion tolerance is highlighted in Lisa Liss’ story. Linda Ruas shares her love to a wider community of untrained volunteer teachers while Kip Cates provides a gentle reminder for environmental education. George Jacobs introduces quite a current issue on how he implements intersectionality as a life understanding method. If you are seeking for models of life to investigate professional ways to engage communities in order to renew the life you live, this book is not to be missed.